Treating chronic kidney disease in Danish primary care: results from the observational ATLAS study - Morten Lindhardt; Søren Tang Knudsen; Thomas Saxild; Morten Charles; Rikke Borg (BMC Primary Care)
Abstract Objectives To describe the clinical characteristics, comorbidity, and medical treatment in a primary care population with chronic kidney disease (CKD). Additionally, to investigate how primary care physicians (PCPs) diagnose, manage and treat impaired kidney function, including uptake of cardio-renoprotective renin–angiotensin–aldosterone system inhibitors (RAASis) and sodium glucose co-transporter 2 inhibitors (SGLT2is). Design An observational study of CKD prevalence, treatment patterns and comorbidities in primary care based on patient record data combined with a questionnaire on diagnosis, management and treatment of impaired kidney function in a real-world, primary care setting. Setting In all 128 primary care clinics in Denmark of 211 randomly invited and a quetionnaire completed by 125/128 participating PCPs. Methods A computerized selection identified 12 random individuals with CKD per clinic with ≥ 2 measurements of eGFR < 60 mL/min/1.73 m2 or UACR > 30 mg/g within two years (N = 1 497). Pre-specified data collected from individual electronic health records included demographics, clinical variables, comorbidities, and relevant prescribed medications. Results Of the CKD study population (N = 1 497), 80% had hypertension, 32% diabetes (DM), 13% heart failure (HF), 59% no DM/HF. ACEis/ARBs were prescribed to 65%, statins to 56%, SGTL2is to 14%, and MRAs to 8% of all individuals. Treatment patterns differed between individuals with varying comorbidities, e.g., ACEis/ARBs usage was higher in DM (76%) or HF (74%) vs. no DM/HF (58%), as was statin usage (76% in DM vs. 45% in no DM/HF). SGTL2i usage in no DM/HF was low. Most PCPs identified CKD using eGFR < 60 mL/min/1.73 m2 (62%) or UACR > 30 mg/g (58%) and 62% reported initiating treatment to retard kidney function decline. Conclusions Despite good PCP awareness and wish to use relevant guidelines, a gap exists in implementation of cardio-renoprotective treatment, especially in individuals without DM/HF. This offers an opportunity for clear recommendations to PCPs to optimize early cardio-renal protection in individuals with CKD.